2001
DOI: 10.1080/02688690120082468
|View full text |Cite
|
Sign up to set email alerts
|

Chronic posttraumatic movement disorder alleviated by insertion of meso-diencephalic deep brain stimulating electrode

Abstract: Incapacitating and drug-resistant posttraumatic movement disorders have successfully been treated by stereotactic thalamotomy. We describe the case of a young man with a posttraumatic hemiballismoid type movement disorder of the left arm, persistent for 2 years, who was selected for treatment with a thalamic deep brain stimulator. However, placement of the stimulating electrode tip at the junction of the zona incerta and subthalamic regions caused abolition of the movement disorder, and the pulse generator was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Additional cerebellar signs often reported after subthalamotomies, and which we also observed during evaluation of the stimulation settings, included hypotonia, [13] 1 SCA type 2 bilateral none reported Hooper et al [12] 1 PTT unilateral none reported Kitagawa et al [11] 1 ET unilateral 1 DT unilateral none reported Kitagawa et al [8] 8 PD unilateral none reported Murata et al [10] 8 ET unilateral none reported Plaha et al [5] 4 ET unilateral none reported Plaha et al [7] 13 PD bilateral 1 PD unilateral none reported Plaha et al [6] 6 dysmetria and disturbance of gait or balance [27][28][29] . In one study by Blacker et al [29] , all patients demonstrated a postoperative hypotonia combined with slight transient clumsiness of the affected limb after subthalamotomy.…”
Section: Stimulation-induced Side Effectsmentioning
confidence: 63%
See 1 more Smart Citation
“…Additional cerebellar signs often reported after subthalamotomies, and which we also observed during evaluation of the stimulation settings, included hypotonia, [13] 1 SCA type 2 bilateral none reported Hooper et al [12] 1 PTT unilateral none reported Kitagawa et al [11] 1 ET unilateral 1 DT unilateral none reported Kitagawa et al [8] 8 PD unilateral none reported Murata et al [10] 8 ET unilateral none reported Plaha et al [5] 4 ET unilateral none reported Plaha et al [7] 13 PD bilateral 1 PD unilateral none reported Plaha et al [6] 6 dysmetria and disturbance of gait or balance [27][28][29] . In one study by Blacker et al [29] , all patients demonstrated a postoperative hypotonia combined with slight transient clumsiness of the affected limb after subthalamotomy.…”
Section: Stimulation-induced Side Effectsmentioning
confidence: 63%
“…The modern reports concerning DBS in the PSA are limited to 70 patients, of which 42 were treated for PD [1,[6][7][8][9] , 18 for essential tremor [5,6,10,11] , and the remaining 10 patients for other forms of tremor [6,[11][12][13] . The complications encountered in these studies were generally few and mild ( table 2 ).…”
Section: Psa In the Treatment Of Movement Disordersmentioning
confidence: 99%
“…Since the first modern study concerning PSA DBS in the year 2000 the results from 70 patients have been reported in 10 studies 10, 11, 15, 16, 18–22, 35. Eighteen of theses patients were operated for ET 15, 17, 18, 36.…”
Section: Discussionmentioning
confidence: 99%
“…Thousands of patients underwent subthalamotomies in the PSA during the following years, but the interest for applying DBS to this area has been limited 8–10. Since 1977, 13 articles have presented a total of 80 patients operated with PSA DBS for a variety of disorders 10–22. Four of these reported the results from 18 patients treated for ET 15, 17, 18, 22.…”
mentioning
confidence: 99%
“…Current hypotheses involve neuroaugmentive and neurosuppressive effects on neural network functioning, including the concept of jamming. 3 Given that similar clinical responses occur after stereotactic lesioning and stimulation procedures, 13,21,22 the interpretation of the responsible mechanism becomes even more complex. Nevertheless, stimulation techniques are considered to be safer and are reversible and therefore recommended in patients with substantial brain damage.…”
Section: Discussionmentioning
confidence: 99%